Pengaruh Stres Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan di PT Yamaha Motor Electronics Indonesia Bekasi - Frida Aprilia Pratiwi (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This study aims to examine and analyze the influence of work stress and work environment on employee performance at PT Yamaha Motor Electronics Indonesia. The research involved 50 respondents selected using a purposive sampling technique, targeting employees who have worked for at least one year. Data collection methods included questionnaires, observation, and literature study. The data were analyzed using data quality tests (validity and reliability), classical assumption tests, multiple linear regression analysis, hypothesis testing (t-test and F-test), and the coefficient of determination (R²), all processed with the assistance of SPSS version 25.The results showed that, based on the partial t-test, the work stress variable had a negative and significant effect on employee performance with a t value of -7.862 > t table 2.011, while the work environment variable had a positive and significant effect with a t value of 5.543 > t table 2.011. Simultaneously, both variables significantly affected employee performance, as indicated by an F value of 43.229 > F table 3.20 and a significance value of 0.000. The Adjusted R Square value of 0.633 indicates that 63.3% of the variation in employee performance can be explained by work stress and work environment.